The VPS4 component of the ESCRT machinery plays an essential role in HPV infectious entry and capsid disassembly - Broniarczyk, Justyna (Sci Rep, 2017)
Human Papillomavirus (HPV) infection involves multiple steps, from cell attachment, through endocytic trafficking towards the trans-Golgi network, and, ultimately, the entry into the nucleus during mitosis. An essential viral protein in infectious entry is the minor capsid protein L2, which engages different components of the endocytic sorting machinery during this process. The ESCRT machinery is one such component that seems to play an important role in the early stages of infection. Here we have analysed the role of specific ESCRT components in HPV infection, and we find an essential role for VPS4. Loss of VPS4 blocks infection with multiple PV types, suggesting an evolutionarily conserved critical step in infectious entry. Intriguingly, both L1 and L2 can interact with VPS4, and appear to be in complex with VPS4 during the early stages of virus infection. By using cell lines stably expressing a dominant-negative mutant form of VPS4, we also show that loss of VPS4 ATPase activity results in a marked delay in capsid uncoating, resulting in a defect in the endocytic transport of incoming PsVs. These results demonstrate that the ESCRT machinery, and in particular VPS4, plays a critical role in the early stages of PV infection.